Study of the Work of the Boundary Layers of Lubricants Materials (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article analyzes and studies the work of the boundary layers of lubricants in the process of operation. The performance of the boundary layer of oil is determined by the interaction of the molecular film of the oil with the rubbing surface of the metal. In the process of work, the composition of lubricants becomes more complicated due to the oxidation of thermochemical decomposition of hydrocarbons and additives. These products enter into physical and chemical interactions with each other and with contaminants coming from outside. Lubricants containing surfactants have the ability to adsorb on the interface surfaces of two media: liquid and solid